Anticancer Drug-Incorporated Layered Double Hydroxide Nanohybrids and Their Enhanced Anticancer Therapeutic Efficacy in Combination Cancer Treatment. (17th April 2014) - Kim, Tae-Hyun; Lee, Gyeong Jin; Kang, Joo-Hee; Kim, Hyoung-Jun; Kim, Tae-il; Oh, Jae-Min
Abstract : Objective . Layered double hydroxide (LDH) nanoparticles have been studied as cellular delivery carriers for anionic anticancer agents. As MTX and 5-FU are clinically utilized anticancer drugs in combination therapy, we aimed to enhance the therapeutic performance with the help of LDH nanoparticles. Method . Anticancer drugs, MTX and 5-FU, and their combination, were incorporated into LDH by reconstruction method. Simply, LDHs were thermally pretreated at 400°C, and then reacted with drug solution to simultaneously form drug-incorporated LDH. Thus prepared MTX/LDH (ML), 5-FU/LDH (FL), and (MTX + 5-FU)/LDH (MFL) nanohybrids were characterized by X-ray diffractometer, scanning electron microscopy, infrared spectroscopy, thermal analysis, zeta potential measurement, dynamic light scattering, and so forth. The nanohybrids were administrated to the human cervical adenocarcinoma, HeLa cells, in concentration-dependent manner, comparing with drug itself to verify the enhanced therapeutic efficacy. Conclusion . All the nanohybrids successfully accommodated intended drug molecules in their house-of-card-like structures during reconstruction reaction. It was found that the anticancer efficacy of MFL nanohybrid was higher than other nanohybrids, free drugs, or their mixtures, which means the multidrug-incorporated LDH nanohybrids could be potential drug delivery carriers for efficient cancer treatment via combination therapy.